Possible role of S-equol on bone loss via amelioration of inflammatory indices in ovariectomized mice - Nishide, Yoriko (the Society for Free Radical Research Japan, 2013)
S-equol is a natural metabolite of the soy isoflavone, daidzein, produced by intestinal bacteria. S-equol has been shown to have greater estrogenic activity than other soy isoflavones and prevent bone loss in post-menopausal women. Estrogen regulates both bone remodeling and hemopoiesis in the bone marrow, these processes that communicate closely with each other. In this study, we investigated the effect of S-equol on bone mass and gene expression of bone marrow cells in ovariectomized (OVX) mice. Female ddY strain mice, aged 12 weeks, were either sham operated or OVX. The OVX mice were randomly divided into two groups: (1) OVX control and (2) OVX fed a 0.06% (w/w) S-equol supplemented diet. After 2 weeks, the trabecular bone volume of the femoral distal metaphysis was markedly reduced in OVX mice. However, treatment with equol was observed to ameliorate this. Expression of inflammatory-, osteoclastogenesis- and adipogenesis-related genes was increased in OVX mice compared with sham mice, and equol was observed to suppress their expression. The present study demonstrates that equol might ameliorate bone loss caused by estrogen deficiency through regulating hemopoiesis and production of inflammatory cytokines in bone marrow cells.